1984
DOI: 10.1073/pnas.81.13.4023
|View full text |Cite
|
Sign up to set email alerts
|

Altered mRNA splicing in monkey cells abortively infected with human adenovirus may be responsible for inefficient synthesis of the virion fiber polypeptide.

Abstract: Messenger RNA encoding the fiber protein of the human adenovirus serotype 2 (Ad2) capsid is inefficiently translated in abortively infected African green monkey kidney cells. The amount of fiber mRNA present in the cytoplasm of abortively infected monkey cells is less than that in productively infected cells by a factor of 5-10 but synthesis of the fiber polypeptide is reduced by a factor of more than 100. Evidence from a variety of experiments indicates that the defect does not lie in the translational appara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Studies with DBP hr mutants, which efficiently multiply in monkey cells, indicate that changes in this protein can directly or indirectly alter the patterns of splicing of late viral transcripts-in particular, those processed into fiber mRNA (17,18). Moreover, the translatability of the fiber mRNA in vivo is affected by these hr mutations, which may or may not be a consequence of the altered structure of the message.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with DBP hr mutants, which efficiently multiply in monkey cells, indicate that changes in this protein can directly or indirectly alter the patterns of splicing of late viral transcripts-in particular, those processed into fiber mRNA (17,18). Moreover, the translatability of the fiber mRNA in vivo is affected by these hr mutations, which may or may not be a consequence of the altered structure of the message.…”
Section: Discussionmentioning
confidence: 99%
“…The purported negative regulation of early genes mediated by wild-type (wt) DBP appears to operate at the transcription level for E4 (12,13) and at the level of mRNA turnover for regions EIA, EIB, and probably E2A (14). However, studies by Rice and Klessig (15) (16), alterations in the pattern of mRNA splicing for the fiber polypeptide (17,18), and poor utilization of this mRNA in vivo (19). Host-range (hr) mutants of Ad, which overcome these blocks and thus are capable of productive growth in monkey cells, contain alterations in the DBP gene (20)(21)(22).…”
mentioning
confidence: 99%
“…It has been hypothesized over the last two decades that this is a 2-fold defect that is manifested not only in transcription but also as an impediment in translation of the protein due to incomplete splicing or incomplete maturation of the fiber mRNA. This host cell restriction on translation was overcome by cotransfection with SV40 (17)(18)(19)(20). SV40 DNA provided unknown factors necessary to allow the progression of the adenovirus type 2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Defective splicing of the Li transcripts (little or no Illa mRNA) and fiber transcripts (altered patterns of ancillary leaders on the mRNA) in abortively infected monkey cells is overcome by host range mutations in the adenovirus DBP or the presence of the SV40 T antigen (3,4,27 Li transcripts from pK3, a vector containing large deletions both 5' and 3' of the Illa splice junction, were spliced to the Illa acceptor in the presence of T antigen. This result suggests that a cis-acting element(s) essential for T-antigen induction of Illa acceptor usage is located within a region of 132 nt 5' and 130 nt 3' of the Illa splice junction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Forbes et al (17) reported cell cycle-dependent variations in small nuclear ribonucleoprotein concentration, which could affect splicing. i Our earlier studies indicated that T antigen, as well as DBP, could affect RNA splicing in monkey cells (4,27). Here we demonstrate that an SV40 early gene product (presumably large T antigen) alters Li transcript splicing in human cells as well as in monkey cells.…”
Section: Discussionmentioning
confidence: 99%